ETIKA, PROFESI DOSEN DAN PERGURUAN TINGGI: SEBUAH KAJIAN KONSEPTUAL - Arum Ardianingsih; Siti Yunitarini (Jurnal Ekonomi Dan Bisnis, 2015)
University is place to produced of professional human resource for have qualification in science area and ethical behaviour. Universities have a duty to establish "charater building" student. college consists of several components, namely faculty, students and curriculum. diantaran most important component is the lecturer. so as to ensure that college education is better then the required ethics. The first portion of this paper will examine the role and function of higher education, the importance of ethics for both college and the third the importance of ethics for the profession of teacher.Keywords: college, ethical issues and professional ethics